The sacralization of straightedge punk - Dines, Mike (Muzikološki zbornik, 2014)
This article explores the formation of Krishnacore, a phenomenon born from the amalgamation of American straightedge punk and the Hare Krishna Movement in the 1990s. It argues that whilst shared choices of lifestyle, such as vegetarianism and a distaste for intoxicants and illicit sex, were core tenets towards the conception of the scene, it was bhakti-yoga (the theological and philosophical basis of the Hare Krishna Movement) that cemented such a relationship. Furthermore, it also explores the aesthetic context of punk within a Vedic context, in particular with reference to what is termed as 'Nada-Brahma', or the sacralisation of sound.
Keywords: bhakti-joga; Krishnacore; Nada-Brahma; punk; sakralizacija zvoka; straightedge